Accelerating visual anticipation in sport through temporal occlusion training: a meta-analysis - Müller, S.; Morris-Binelli, K.; Hambrick, D. Z.; Macnamara, B. N. (Sports Medicine, 2024)
Background: The video-based temporal occlusion paradigm has been consistently used in visual anticipation sport research. Objective: This meta-analysis investigated the magnitude to which video-based temporal occlusion training could improve anticipation skill with transfer to representative laboratory and field tasks. Methods: As there are considerably fewer anticipation training than performance studies, the meta-analysis included 12 intervention studies with 25 effect sizes where video simulation and/or field-based tests were used. The Downs and Black checklist adapted for sports science research was used to assess methodological quality of the included studies. Decision time and accuracy of anticipation were the outcome measures because both are relevant to sports skills. The changes in these measures between experimental and control groups from baseline to the transfer test context were used to calculate the magnitude of the training effect. Results: Findings revealed a significant training effect, including a large meta-analytic effect size, and no difference in training benefit across video and field-based transfer tests. Publication bias analyses were inconclusive, likely due to the small number of available studies. Conclusions: These findings are evidence that the temporal occlusion paradigm is an effective method to improve visual anticipation skill across representative perceptual and perceptual-motor transfer tests. The theoretical implication based upon the two-stage model of visual anticipation is that temporal occlusion training can improve use of early information for body positioning by the performer, which could in turn lead to improved execution of the skill goal.